To find the recursive formula for the given arithmetic sequence 7, 5, 3, 1, -1, ..., we can observe the pattern of the sequence.
-
Identify the first term: \( a_1 = 7 \)
-
Determine the common difference: The difference between consecutive terms is: \( 5 - 7 = -2 \)
\( 3 - 5 = -2 \)
\( 1 - 3 = -2 \)
\( -1 - 1 = -2 \)So, the common difference \( d = -2 \).
-
Write the recursive formula: The general form of a recursive formula for an arithmetic sequence is: \( a_n = a_{n-1} + d \) In this case, since the common difference \( d = -2 \), we have: \( a_n = a_{n-1} - 2 \)
Putting this together, the recursive formula is:
- \( a_1 = 7 \)
- \( a_n = a_{n-1} - 2 \)
Thus, the correct response is:
a1=7, an=an−1−2
\( a_1 = 7, \quad a_n = a_{n-1} - 2 \)